Human Neural Tissues from Neural Stem Cells Using Conductive Biogel and Printed Polymer Microelectrode Arrays for 3D Electrical Stimulation. Issue 15 (6th June 2019) - Tomaskovic‐Crook, Eva; Zhang, Peikai; Ahtiainen, Annika; Kaisvuo, Heidi; Lee, Chong‐Yong; Beirne, Stephen; Aqrawe, Zaid; Svirskis, Darren; Hyttinen, Jari; Wallace, Gordon G.; Travas‐Sejdic, Jadranka; Crook, Jeremy M.
Abstract: Electricity is important in the physiology and development of human tissues such as embryonic and fetal development, and tissue regeneration for wound healing. Accordingly, electrical stimulation (ES) is increasingly being applied to influence cell behavior and function for a biomimetic approach to in vitro cell culture and tissue engineering. Here, the application of conductive polymer (CP) poly(3, 4‐ethylenedioxythiophene)‐polystyrenesulfonate (PEDOT:PSS) pillars is described, direct‐write printed in an array format, for 3D ES of maturing neural tissues that are derived from human neural stem cells (NSCs). NSCs are initially encapsulated within a conductive polysaccharide‐based biogel interfaced with the CP pillar microelectrode arrays (MEAs), followed by differentiation in situ to neurons and supporting neuroglia during stimulation. Electrochemical properties of the pillar electrodes and the biogel support their electrical performance. Remarkably, stimulated constructs are characterized by widespread tracts of high‐density mature neurons and enhanced maturation of functional neural networks. Formation of tissues using the 3D MEAs substantiates the platform for advanced clinically relevant neural tissue induction, with the system likely amendable to diverse cell types to create other neural and non‐neural tissues. The platform may be useful for both research and translation, including modeling tissue development, function and dysfunction, electroceuticals, drug screening, and regenerative medicine. Abstract : An array of printed polymer pillar microelectrodes is interfaced with an electrically conductive biogel encapsulating human neural stem cells for 3D electrical stimulation of developing neural tissue. Stimulation enhances tissue maturation evidenced by widespread tracts of high‐density mature neurons, and functional neural networks with increased response to drug‐induced disinhibition. The platform is scaleable and amenable for research and translation.